CVID Associated with Systemic Amyloidosis - Saliha Esenboga; Deniz Çagdas Ayvaz; Arzu Saglam Ayhan; Banu Peynircioglu; Ozden Sanal; Ilhan Tezcan (Case Reports in Immunology)
Common variable immunodeficiency (CVID) is a frequent primary immune deficiency (PID), which consists of a heterogeneous group of disorders and can present with recurrent infections, chronic diarrhea, autoimmunity, chronic pulmonary and gastrointestinal diseases, and malignancy. Secondary amyloidosis is an uncommon complication of CVID. We report an unusual case of a 27-year-old male patient who presented with recurrent sinopulmonary infections, chronic diarrhea, and hypogammaglobulinemia and was diagnosed with CVID. The patient was treated with intravenous immunoglobulin (IVIg) therapy once every 21 days and daily trimethoprim-sulfamethoxazole for prophylaxis. Two years after initial diagnosis, the patient was found to have progressive decline in IgG levels (as low as 200–300 mg/dL) despite regular Ig infusions. The laboratory tests revealed massive proteinuria and his kidney biopsy showed accumulation of AA type amyloid. We believe that the delay in the diagnosis of CVID and initiation of Ig replacement therapy caused chronic inflammation due to recurrent infections in our patient and this led to an uncommon and life-threatening complication, amyloidosis. Patients with CVID require regular follow-up for the control of infections and assessment of adequacy of Ig replacement therapy. Amyloidosis should be kept in the differential diagnosis when managing patients with CVID.